2014
DOI: 10.2217/bmm.14.10
|View full text |Cite
|
Sign up to set email alerts
|

Serum HER2 Extracellular Domain as a Potential Alternative for Tissue HER2 Status in Metastatic Gastric Cancer Patients

Abstract: Levels of serum HER2 ECD are highly correlated with tissue HER2 status in metastatic gastric cancer. Serum HER2 ECD assay can be considered as a potential alternative for tissue HER2 status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
1
11
1
Order By: Relevance
“…Changes in circulating HER2 levels during chemotherapy were reported to be associated with clinical outcomes in HER2-positive gastric cancer patients receiving trastuzumab and chemotherapy [21,22]. Although we observed a decrease in serum HER2 levels in our study, such decreases simply appeared to reflect tumor shrinkage.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Changes in circulating HER2 levels during chemotherapy were reported to be associated with clinical outcomes in HER2-positive gastric cancer patients receiving trastuzumab and chemotherapy [21,22]. Although we observed a decrease in serum HER2 levels in our study, such decreases simply appeared to reflect tumor shrinkage.…”
Section: Discussioncontrasting
confidence: 74%
“…Circulating HER2 was expected to be a predictive marker for HER2 expression in gastric cancer tissues. Several studies have shown a significant correlation between serum HER2 levels and tissue HER2 expression [21][22][23]. However, in our study, serum HER2 levels ranged from undetectable to extremely high, even though our cohort was limited to patients with high-HER2-expressing tumors.…”
Section: Discussionmentioning
confidence: 63%
“…These results suggest that serum HER2 level elevates when HER2-positive breast cancer metastasizes to distant organs. To the best of our knowledge, only seven studies [16][17][18][19][20][21][22] to date have investigated the serum HER2 level in gastric cancer and results were conflicting like breast cancer: five studies [16,[19][20][21][22]] demonstrated significant correlation between serum and tissue HER2 levels while two [17,18] did not. Similar to the condition of breast cancer studies, the latter included only 13% [17] or no [18] metastatic gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, high serum HER2 ECD levels in patients with metastatic breast cancer were correlated with high risk of disease progression, decreased survival, and reduced response to treatment[11-13]. Several studies have also investigated the clinical significance of serum HER2 ECD in gastric cancer[14-16]. However, differences in detection methods and patient enrollment across studies have led to inconsistent results regarding the associations among serum HER2 ECD concentrations, tissue HER2 status, and patient outcome.…”
Section: Introductionmentioning
confidence: 99%